2010–2011 Queensland floods: Using Haddon's Matrix to define and categorise public safety strategies. (25th July 2013) - Zhong, Shuang; Clark, Michele; Hou, Xiang‐Yu; Zang, Yu‐Li; FitzGerald, Gerry
Abstract: Objective: The 2010–2011 Queensland floods resulted in the most deaths from a single flood event in Australia since 1916. This article analyses the information on these deaths for comparison with those from previous floods in modern Australia in an attempt to identify factors that have contributed to those deaths. Haddon's Matrix, originally designed for prevention of road trauma, offers a framework for understanding the interplay between contributing factors and helps facilitate a clearer understanding of the varied strategies required to ensure people's safety for particular flood types. Methods: Public reports and flood relevant literature were searched using key words 'flood', 'fatality', 'mortality', 'death', 'injury' and 'victim' through Google Scholar, PubMed, ProQuest and EBSCO. Data relating to reported deaths during the 2010–2011 Queensland floods, and relevant data of previous Australian flood fatality (1997–2009) were collected from these available sources. These sources were also used to identify contributing factors. Results: There were 33 deaths directly attributed to the event, of which 54.5% were swept away in a flash flood on 10 January 2011. A further 15.1% of fatalities were caused by inappropriate behaviours. This is different to floods in modern Australia where over 90% of deaths are related to the choices made by individuals. There is no single reason why people drown in floods, but rather a complex interplay of factors. Conclusions: The present study and its integration of research findings and conceptual frameworks might assist governments and communities to develop policies and strategies to prevent flood injury and fatalities.